2023
DOI: 10.30812/matrik.v22i2.2515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Class Imbalance Handling on Datasets Toward Classification Algorithm Performance

Cherfly Kaope,
Yoga Pristyanto

Abstract: Class imbalance is a condition where the amount of data in the minority class is smaller than that of the majority class. The impact of the class imbalance in the dataset is the occurrence of minority class misclassification, so it can affect classification performance. Various approaches have been taken to deal with the problem of class imbalances such as the data level approach, algorithmic level approach, and cost-sensitive learning. At the data level, one of the methods used is to apply the sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has special gates that control how long memories are kept, which makes it easier to learn a lot from data sequences. Studies have shown that it is good at predicting time series data, with LSTM making average predictions that are 85% better than ARIMA [20,1,21]. On the other hand, the Random Forest technique stands out as a strong competitor that can handle complex and nonlinear datasets well.…”
Section: Introductionmentioning
confidence: 99%
“…It has special gates that control how long memories are kept, which makes it easier to learn a lot from data sequences. Studies have shown that it is good at predicting time series data, with LSTM making average predictions that are 85% better than ARIMA [20,1,21]. On the other hand, the Random Forest technique stands out as a strong competitor that can handle complex and nonlinear datasets well.…”
Section: Introductionmentioning
confidence: 99%